Activity of compounds of natural origin against Alicyclobacillus acidoterrestris, a common fruit juices contaminant - Tyfa, Agnieszka; Kunicka-Styczyńska, Alina; Dąbrowska, Justyna (Lodz University of Technology Press, 2015)
Fruit product industry struggles with emerging problem of microbial contamination with Alicyclobacillus acidoterrestris. This acidothermophilic, soil-borne and sporeforming bacterium posses ability to survive commercial pasteurization and thus may cause fruit juices spoilage. Even modern technologies are not effective enough to eliminate A. acidoterrestris from the industrial environments. The green consumer attitude and safety standards suggest adaptation of natural and safe solutions. This paper summarizes the bioactivity of compounds of natural origin which could serve as anti-alicyclobacilli preservation agents maintaining stability of fruit juices.
Keywords: Alicyclobacillus acidoterrestris; essential oils; bacteriocins; fruit products spoilage; antimicrobial activity; Alicyclobacillus acidoterrestris; olejki eteryczne; bakteriocyny; psucie się produktów owocowych; działanie przeciwbakteryjne